Edukasi Dagusibu Obat Sediaan Cair Pada Masyarakat Dusun Kasihan - Rissa, Mexsi Mutia (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2023)
Cases of Atypical Progressive Acute Kidney Injury (GGAPA) / (Atypical Progressive Acute Kidney Injury) in children continue to grow. The incidence of acute kidney failure in children is thought to be caused by some of the ingredients in the syrup preparations. The content of the drug syrup that is suspected of causing acute kidney failure is the syrup containing EG and DEG contaminants. Regarding the problems that occurred with the syrup preparations, observations were made of PKK women in Kasihan Hamlet RT 08, Tamantirto, Kasihan, Bantul, so that many women panicked excessively and did not want to use liquid preparations, including syrups, emulsions, suspensions and other liquid preparations because of the acute renal failure case. So that there is a need for education regarding DAGUSIBU for liquid dosage forms because, DAGUSIBU is a program to improve how to manage drugs properly and correctly, namely through information on how to obtain (DA), use (GU), store (SI) and dispose (BU). medication properly. DAGUSIBU is one of the applications of the Smart Community Movement on Drugs (Gema Careful) activities. The purpose of the service is to increase public knowledge, especially PKK women in Kasihan Hamlet, RT 08, Tamantirto, Bantul about DAGUSIBU, a syrup preparation drug. The direct counseling method is carried out through offline presentations using slides (power point). The results of community service show positive results. there was a significant increase in public knowledge, which can be seen from the percentage of scores obtained by the community, namely 86.67% and the percentage of posttest scores obtained by participants, namely 88.57%.